Contribution of Prerequisite Materials and Creative Thinking to the Ability of Solving Logarithm Problems at SMK Negeri 4 Medan - Siti Aminah Manurung; Irvan .; Marah Doly Nasution (UMSU, 2023)
The problem in this study is how the mastery of students in exponentiation and root to the ability of students in solving problems of logarithms whether there is a contribution of exponentiation and root on students' ability to solve logarithmic problems.The purpose of this study is to determine the mastery of students in exponentiation and root on students' ability to solve logarithmic problems, to find out whether there is a contribution of exponentiation and root on students' logarithmic learning outcomes and to find out how much the contribution of mastery of exponentiation and root on students' logarithmic learning outcomes.The method of this research was descriptive. As the population of this research was the students of SMK N 4 Medan Class X which were 123 people. The sampling technique used a sample of 25% which was 30 people. The research instrument used was an objective test which consisted of 40 questions.From the results of this study, the data obtained on the proficiency of the students in learning mathematics on the subject of exponentiation and root (variable x) resulted in an average value of 6.93 and a standard deviation of 1.32. While the results of the students' learning in solving logarithmic problems (variable y) resulted in a mean value of 6.92 and a standard deviation of 1.49.Pearson's Product Moment Correlation statistic was used to test the hypotheses. The normality and linearity tests were calculated prior to hypothesis testing. From the results of the analysis it was found that the sample was normally distributed and had a linear regression shown by the equation y = 4.83 + 0.301 x r criticism, which is by comparing the value of rcount with the value of rtable with a real level of ? = 0.05. The value r = 0.27 is obtained from the calculation. This value is greater than the table for n = 30 students of 0.03. Therefore, Ho is rejected and Ha is accepted, which means that there is an effect of students' mastery of exponentiation and root on students' ability to solve logarithmic problems in Class X SMKN 4 Medan.